1998
DOI: 10.1136/hrt.79.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ventricular preexcitation in Japanese schoolchildren

Abstract: Background-WolV-Parkinson-White syndrome is thought to be a congenital disease, however, its exact prevalence is not known. This may be because of the intermittent activity of accessory pathways in some cases and fluctuations in autonomic tone. Aims-To investigate the prevalence of ventricular preexcitation by electrocardiography and reported symptoms in each school age child in Yamanashi prefecture. Methods-From 1994 to 1996, answers to a questionnaire, results of physical examination, and electrocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 18 publications
3
33
1
4
Order By: Relevance
“…62 In another study from 1994 to 1996, 0.1% of Japanese schoolchildren (100 of 92 000) were identified as having WPW. 63 …”
Section: Ecg Screening In Japanmentioning
confidence: 99%
“…62 In another study from 1994 to 1996, 0.1% of Japanese schoolchildren (100 of 92 000) were identified as having WPW. 63 …”
Section: Ecg Screening In Japanmentioning
confidence: 99%
“…The majority of APs conduct antegradely, as seen in patients with WolffParkinson-White (WPW) syndrome (OMIM No. 194200; incidence in general population 1.5 per 1000 persons 25 ; the prevalence of WPW syndrome in children under 13 years of age is lower, at 0.07% 26 ). In adults, 25% of APs involved in AVRT are concealed, which indicates that they only have retrograde conducting properties.…”
Section: Discussionmentioning
confidence: 99%
“…5 The increased frequency in males is in accordance with previous reports 3 5 10 ; however, Sano et al recently reported a 1:1 male to female ratio in Japanese schoolchildren with ventricular pre-excitation. 11 The highest incidence in female subjects in our study was during the seventh decade (fig 1). Interestingly this peak [22][23][24][25][26]1998), we cannot exclude the possibility that women's access to health care is less or later in their life than men's.…”
Section: Demographic Featuresmentioning
confidence: 88%